2018
DOI: 10.1136/bjophthalmol-2018-312401
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and comparability of peripapillary vessel density measurements of high-density and non-high-density optical coherence tomography angiography scans in normal and glaucoma eyes

Abstract: VD of HD scans was higher than that of non-HD scans. The wide 95% LoA indicates that the VD measurements of HD and non-HD scans cannot be used interchangeably. Test-retest repeatability of VDs on HD scans was as high as 6%. These results should be considered while using OCTA for longitudinal evaluation of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…Venugopal et al. (,) also reported that SS of the scans had a significant effect on the short‐term repeatability of OCTA VDs. However, the differences in SS between the two measurements were the only significant factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Venugopal et al. (,) also reported that SS of the scans had a significant effect on the short‐term repeatability of OCTA VDs. However, the differences in SS between the two measurements were the only significant factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 95%
“…; Venugopal et al. ,). However, the long‐term repeatability of such parameters has not been reported as far as we know.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to nailfold capillary alterations, the retina is another vulnerable organ to vascular dysregulation. Ganglion cell complex (GCC) thickness and RPC density are important indicators for detecting retinal ganglion cell (RGC) damage (Shin et al 2017; Venugopal & Rao 2018; Venugopal & Rao 2019). In this study, parafoveal GCC thickness was positively related to nailfold capillary density in POAG eyes.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Moreover, quantitative OCTA measurements have high repeatability. 16,17 Studies using OCTA have shown that glaucoma patients have significantly lower ocular perfusion than healthy subjects, 18 and decreased VD was correlated with axial length (AL) elongation. 19,20 Furthermore, lower VD, measured by OCTA, was associated with more severe glaucomatous visual field (VF) damage in highly myopic eyes, 21,22 and a larger FAZ area was associated with both glaucoma and high myopia.…”
mentioning
confidence: 99%